Longitudinal Humoral Responses after COVID-19 Vaccination in Peritoneal and Hemodialysis Patients over Twelve Weeks - Speer, Claudius; Schaier, Matthias; Nußhag, Christian; Töllner, Maximilian; Buylaert, Mirabel; Kälble, Florian; Reichel, Paula; Grenz, Julia; Süsal, Caner; Zeier, Martin; Schnitzler, Paul; Morath, Christian; et al. (Vaccines, 2021)
It has been demonstrated that patients on hemo- or peritoneal dialysis are particularly susceptible to SARS-CoV-2 infection and impaired seroconversion compared to healthy controls. Follow-up data on vaccination response in dialysis patients is limited but is greatly needed to individualize and guide (booster) vaccination strategies. In this prospective, multicenter study we measured anti-spike S1 and neutralizing antibodies in 124 hemodialysis patients, 41 peritoneal dialysis patients, and 20 age- and sex-matched healthy controls over 12 weeks after homologous BNT162b2 vaccination. Compared to healthy controls, both hemodialysis and peritoneal dialysis patients had lower anti-S1 IgG antibodies (median (IQR) 7.0 (2.8-24.3) and 21.8 (5.8-103.9) versus 134.9 (23.8-283.6), respectively; p < 0.001 and p < 0.05) and a reduced SARS-CoV-2 spike protein-ACE2 binding inhibition caused by vaccine-induced antibodies (median (IQR) 56% (40-81) and 77% (52-89) versus 96% (90-98), respectively; p < 0.001 and p < 0.01) three weeks after the second vaccination. Twelve weeks after the second vaccination, the spike protein-ACE2 binding inhibition significantly decreased to a median (IQR) of 45% (31-60) in hemodialysis patients and 55% (36-78) in peritoneal dialysis patients, respectively (p < 0.001 and p < 0.05). Peritoneal dialysis patients mounted higher antibody levels compared with hemodialysis patients at all time points during the 12-week follow-up. Individual booster vaccinations in high-risk individuals without seroconversion or rapidly waning neutralizing antibody levels are required and further data on the neutralization of emerging variants of concern in these patients are urgently needed.
Gesehen am 26.11.2021